PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA UPTD PUSKESMAS BANJARANGKAN II - Wijayanthi, Ni Putu Putri Ayu; Widya Goca, I Gusti Putu Agung; Wulan Dewi, Ida Ayu Ghirina (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
Performance is a description of the level of achievement of implementing an activity program or policy in realizing an organization's goals, objectives, vision and mission as outlined through an organization's strategic planning. The aim of the research is to determine the effect of human resource development on employee performance with work motivation as a mediating variable at UPTD Puskesmas Banjarangkan II. The number of samples was determined using a non-probability sampling method with a saturated sampling technique, namely 83 respondents. Data were analyzed using descriptive statistical analysis, inferential statistics and testing mediating variables. The results of the research show that human resource development has a positive and significant effect on employee performance, human resource development has a positive and significant effect on work motivation, work motivation has a positive and significant effect on employee performance and human resource development has a positive and significant effect on employee performance with motivation work as a mediating variable at UPTD Puskesmas Banjarangkan II.